2018
DOI: 10.1177/1533033818785512
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy Mediated by Aloe-Emodin Inhibited Angiogenesis and Cell Metastasis Through Activating MAPK Signaling Pathway on HUVECs

Abstract: Photodynamic therapy is a clinically used, minimally invasive therapeutic procedure that involves the application of photosensitizers which can locate in target cells and so be irradiated at a corresponding wavelength. Laser light irradiation activation of photosensitizers generates free reactive oxygen species, which induces selective cytotoxic activity in target cells. Within recent years, aloe-emodin as a photosensitizer has been successfully applied in photodynamic therapy applications. Angiogenesis plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…The MAPK pathway, known as a cascade of protein kinases, is closely associated with the tumorigenesis in multiple malignancies. [50][51][52] The activation of MAPK pathway could stimulate various oncogenic systems including EMT, which transferred epithelial characteristics into mesenchymal phenotype, finally leading tumors getting migratory and invasive features. 53 Consistently, our study also demonstrated that overexpression of CIC inhibited the proliferative and invasion of RCC cells in vivo through suppressing the activation of MAPK pathway, which indicated that MAPK pathway might be involved in the regulation of miR-106b/CIC axis during proliferation and metastasis in RCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway, known as a cascade of protein kinases, is closely associated with the tumorigenesis in multiple malignancies. [50][51][52] The activation of MAPK pathway could stimulate various oncogenic systems including EMT, which transferred epithelial characteristics into mesenchymal phenotype, finally leading tumors getting migratory and invasive features. 53 Consistently, our study also demonstrated that overexpression of CIC inhibited the proliferative and invasion of RCC cells in vivo through suppressing the activation of MAPK pathway, which indicated that MAPK pathway might be involved in the regulation of miR-106b/CIC axis during proliferation and metastasis in RCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy (PDT), as a valid therapy modality for multiple solid tumors, is minimally invasive and innoxious and possesses selective cytotoxicity for targeted cells [15]. It is based on photosensitizers and laser light with a specific wavelength, causing the production of reactive oxygen species (ROS) and inducing tumor cell apoptosis/necrosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mention processes are connected with the activation of p38, ERK, but not JNK, while the expression of vascular endothelial growth factor was diminished upon the treatment. In addition, AE-PDT altered the organization of F actin cytoskeleton [52].…”
Section: Aloe Emodin As a Sensitizer In Photodynamic Therapymentioning
confidence: 95%